Urgencia del renacimiento y del humanismo hoy - Sobrino Chunga, Lisle (2010)
In today's reality there is a co-existence of many paradigms that affect our lives and concerns. Faculty, educators, and all people who are in the search for the truth and meaning of life attempt to give explanations and apply unconventional explanations that are generative. In addition, they try to give the best solution strategy to a great diversity and multiplicity of questions on "innovative" subjects, concerns, difficulties and/or problems inherent to all human, which is very confusing and sometimes even mistaken, being the conviction of being right the worst of them all.